Applications of Photoredox Catalysis for the Radical-Induced Cleavage of C–C Bonds - Vanderghinste, Jaro; Das, Shoubhik (Synthesis, 2022)
Selective cleavage of C–C bonds forms one of the greatest challenges in current organic chemistry, due to the relative strength of these bonds. However, such transformations are an invaluable instrument to break down and construct new carbon–carbon bonds. To achieve this, photochemistry can be used as a tool to generate radicals and induce the cleavage of these bonds due to their high reactivity. This review examines some of the most influential contributions in this field since 2010.1 Introduction2 C–C Bond Cleavage2.1 Homogeneous Catalyst2.1.1 N-Centered Radical2.2.2 O-Centered Radical2.2 Heterogeneous Catalyst3 C=C Bond Cleavage3.1 Homogeneous Catalyst3.2 Heterogeneous Catalyst4 C≡C Bond Cleavage4.1 Homogeneous Catalyst4.2 Heterogeneous Catalyst5 Conclusion
Keywords: photochemistry; radicals; C–C bond cleavage; visible light; homogeneous; heterogeneous